Acute Infection of a Documented Seminal Vesicle Cyst via Hematogenous Seeding - Palmer, William C; Patel, Neal C; Renew, Johnathan R; Bridges, Mellena D; Stancampiano, Fernando F (Urology Journal, 2014)